Investigating Sex-Related Moderation Effects and Mediation Effects of Self-Control on Delinquency Among Portuguese Youth - Pechorro, Pedro (International journal of offender therapy and comparative criminology, 2021)
Self-control refers to the ability to override impulses and behave in accordance with societal norms. Deficits in self-control are strongly associated with conduct problems, externalizing disorders, crime, and violence. The main aim of the present study is to investigate possible moderation and mediation effects related to self-control. A school sample of male (n = 257, M = 15.97 years, SD = .98 years) and female (n = 213, M = 15.79 years, SD = 1.03 years) youth from Portugal agreed to participate. Moderation analysis revealed that sex moderates the relationship between self-control and aggression, conduct disorder symptoms, and self-reported delinquency. Mediation analysis revealed that self-control mediates the relations between both triarchic psychopathic traits and dark triad traits, and the self-reported juvenile delinquency outcome. The findings suggest that self-control exerts significant effects on the criminal/antisocial-related variables examined among Portuguese youth.